Differential blood counting in fish as a non-destructive biomarker of water contamination exposure - Corrêa, Sandra Aparecida da Silva; Abessa, Denis Moledo de Souza [UNESP]; Santos, Luciana Gomes dos; da Silva, Edison Bezerra; Seriani, Robson [UNESP] (Taylor & Francis, 2017)
Differential white blood cell counting was performed on blood from the fish species Oreochromis niloticus and was used as an in situ indicator of the species’ exposure to contamination. Ten young fish were collected in an area influenced by the discharge of effluents and from a fish farm (control group). The fish were anesthetized and caudal puncture was used to collect the blood. Differential white blood cell counting was performed, as well as the counting of total leukocytes and thrombocytes (in 2000 cells). Physicochemical parameters of the water from both sites were analyzed. The water from the polluted area was found to have high conductivity and low levels of dissolved oxygen, factors that indicate poor environmental quality. Fish collected from the polluted site presented higher percentages of eosinophils and monocytes and fewer thrombocytes because of exposure to pollution and hypoxic conditions. The differential white blood cell count represents a suitable biomarker of environmental health and provides a tool for biomonitoring water quality.
Keywords: aquatic pollution; biomonitoring; Fish; hematology; Oreochromis niloticus; sewage